Prevalence of hypertension and associated risk factors among adult rural women - Khan, NR; Hossain, MM; Ferdousi, SK; Ara, R; Hossain, MZ; Hoque, SR; Deb, SR (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10542 J. Dhaka Med. Coll. 2011; 20(2): 153-158